Ketahanan Ekonomi dan Peacebuilding: Pemberdayaan UMKM OTOP di Kawasan Konflik Thailand Selatan - Murokib Kode (POLITEKNIK LP3I, 2026)
The southern border region of Thailand (Pattani, Yala, and Narathiwat) endures protracted conflict and structural poverty that constrain the economic activities of Malay-Muslim communities. This study analyzes the implementation of the One Tambon One Product (OTOP) program in a conflict zone, identifies the barriers and adaptation mechanisms of entrepreneurs, and evaluates the potential of OTOP as an instrument of economic peacebuilding. A sequential explanatory mixed-methods design was used: a survey of 150 OTOP entrepreneurs (stratified random sampling) and in-depth interviews with 18 informants (purposive sampling), analyzed through descriptive-inferential statistics and thematic analysis. Findings reveal that conflict affects six business dimensions: restricted mobility (73.3%), low trust in government programs (38.7%), difficult access to capital (68%), limited market penetration beyond the region (22%), low e-commerce adoption (29.3%), and psychosocial burden (61.3%). Communities developed four social-capital-based adaptation mechanisms: solidarity networks, mosque-based economic clusters, halal and Malay-Islamic identity specialization, and cross-border market linkages with Malaysia. The study contributes theoretically by integrating conflict-sensitive development, empowerment, and economic peacebuilding into a single analytical framework, and practically by recommending a conflict-sensitive OTOP program design through strengthened Islamic financing and cross-border trade corridors.